(untitled) (Brazilian Journal of Health Research, 2024)
Introduction: Mucopolysaccharidosis type II (MPS II) or Hunter syndrome is defined as an enzyme deficiency of genetic origin, whose inheritance is recessive and X-linked. In this syndrome, there is a mutation in the gene responsible for encoding the enzyme iduronate-2-sulfatase (IDS), leading to the accumulation of glycosaminoglycans (GAGs). Therefore, GAGs accumulate in various organs and tissues, leading to their dysfunction. Case report: This study consists of a case report of this rare syndrome, in which the patient presents suggestive physical characteristics from birth and a family history of a sibling with the same disease, allowing early diagnosis. On physical examination, the patient presents phenotypic manifestations of the disease, such as low nasal bridge and hirsutism. Laboratory tests confirmed the increase in urinary glycosaminoglycans, and the genetic study confirmed an alteration in the IDS gene. With early diagnosis, the patient began intrathecal gene therapy at a specialized center in the South of the country and, despite the limitations of the disease, has shown favorable progress. He is being monitored by a physiotherapist, speech therapist, occupational therapist, pediatrician and geneticist. Conclusion: MPS II is a rare disease, whose most commonly used treatment in Brazil currently involves the management of signs and symptoms. However, advances in hematopoietic stem cell transplantation and enzyme and gene replacement therapies have provided longer survival and quality of life for patients. Healthcare professionals in various specialties should be alerted to ensure early diagnosis and intervention, modifying the natural history of these patients.